Social work reclaimed : innovative frameworks for child and family social work practice - Goodman, Steve; Trowler, Isabelle; Munro, Eileen, 1950- (Philadelphia, PA : Jessica Kingsley Publishers, 2012)
'Reclaiming Social Work (RSW) is a radical new system for delivering child and family social work in the UK. The system was first piloted in the London Borough of Hackney and the model has gained national recognition. At the heart of this innovative system is the endeavour to keep children together with their families. This book sets out what the Reclaiming Social Work model is, how it was implemented, and how it works. It explains the RSW system of social work'units' made up of clinicians and therapists and headed by a consultant social worker, and demonstrates how it has worked in practice. The evidence base and theories underlying the model are also explained. Several chapters are written by consultant social workers with extensive experience of working within RSW, which outline the methodological approaches used. This book on a pioneering new social work model will be of great interest to social work managers, policymakers and academics.'--Publisher's website.
Foreword / Eileen Munro -- Introduction / Isabelle Trowler and Steve Goodman -- A systems methodology for child and family social work / Isabelle Trowler and Steve Goodman -- Systemic practice in a risk managements context / Nick Pendry -- Behavioural-based interventions: social learning theory / Stewart McCafferty -- Stories lived, stories told: using a sstemic approach to case recording n the social work unit / Julie Rooke -- Preconditions: structure, continuity and momentum / Karne Schiltroth -- Working with people in transition / Timo Dobrowolski -- The centrality of relationships / Karen Gaughan and Sonya Kalyniak -- Liberated thinking within a social work unit / Rick Mason -- Helping people move beyond their own histories / Martin Purbrick -- Seen and heard: the unfolding sotry of reclaiming soical work through the eyes of a children's practitioner / Charlie Clayton -- Conclusion and reflections on our journey / Isabelle Trowler and Steve Goodman.
Includes bibliographical references and index.
Keywords: Social work with children -- Great Britain; Family social work -- Great Britain